Cultural Tolerance, Diversity and Pluralism: The Recognition of Yogyakarta as The City of Tolerance - Muhammad Kamil (Universitas Muhammadiyah Malang, 2018)
This paper intends to explore the areas of tolerance and intolerance to the diversity of the people of Yogyakarta amid cultural, racial and religious modernities. The City of Tolerance as an achievement that supports the national-ethnic tolerance of society is unable to create collective action. Structuring the meanings in the culture of the people of Yogyakarta actually gave birth to the expression of conflict and intolerance towards the minority. The pattern of conflictual relationships that sometimes involve violence has altered the structural dynamic order of a harmonious society.